Brillouin Light Scattering of Halide Double Perovskite. Issue 8 (23rd March 2022) - Pang, Simin; Liu, Xinbao; Luo, Jiajun; Xie, Yaru; Tang, Jiang; Meng, Sheng; Tan, Ping‐Heng; Zhang, Jun
Abstract : Cs2 Ag1− x Na x In1− y Bi y Cl6 with high photoluminescence quantum yield (PLQY) and broadband emission due to self‐trapped excitons (STEs) is one of the promising candidates for single‐emitter‐based white light–emitting materials and devices. Considering fundamental physical mechanisms, structure design and performance optimization of devices, comprehensive knowledge of the elasticity, and thermal properties are imperative to understand the formation of STEs in Cs2 Ag1− x Na x In1− y Bi y Cl6 and minimize thermomechanical stresses induced device failure, respectively. However, its elastic and thermal properties are still poorly understood. Herein, the first angle‐resolved Brillouin light scattering (BLS) measurements study for a bulk Cs2 Ag0.4 Na0.6 InCl6 :0.04%Bi 3+ crystal is reported, and the first‐principles calculations of phonon dispersions are used to further validate our experimental results. Using the measured Brillouin frequency shifts, we evaluate the low elasticity of Cs2 Ag0.4 Na0.6 InCl6 :0.04%Bi 3+ : C 11 = 38.63, C 12 = 16.11, and C 44 = 10.20 GPa, which supports the thesis that STEs exist in semiconductors with excitons and a soft lattice. Additionally, an ultralow‐acoustic Debye temperature (87 K) and lattice thermal conductivity (1.03 W m −1 K −1 ) along the [111] direction of Cs2 Ag0.4 Na0.6 InCl6 :0.04%Bi 3+, which indicates the weak interatomic interactions and elasticity are estimated. Furthermore, a general approach is also provided to investigate the elastic and thermal properties of materials with different crystal structures utilizing angle‐resolved BLS spectroscopy. Abstract : Herein, low elastic coefficients and lattice thermal conductivity of Cs2 Ag1− x Na x In1− y Bi y Cl6 halide double perovskite are evaluated using angle‐resolved Brillouin light scattering spectroscopy. The physical quantities obtained here contribute to understanding the self‐trapped excitons (STEs) in halide double perovskites and facilitating future research on designing devices like single‐emitter‐based white light–emitting phosphors and diodes, which incorporate these new materials.